Microwave – Assisted Extraction of Chlorogenic Acid from Coffee liberica L - Josephine Q. Borja; Marylou M Uy; Jose Salvador Lim; Matthew Edson Ong; Alejandro Miguel Ros (ASEAN Journal of Chemical Engineering, 2015)
This study applied microwave-assisted extraction of chlorogenic acid (CGA) from Coffee liberica L. using ethanol as solvent. It sought to determine the effects of temperature, extraction time, solvent-to-solid ratio, and solvent concentration on the CGA yield expressed as gallic acid equivalent per litre (mg GAE L-1). The values of these factors were varied at three levels each and experiments were implemented using the L934 orthogonal array of the Taguchi design of experiment. Results showed that increasing the solvent-to-solid ratio from 2.5 to 7.5 mL g--1decreased the yield significantly. Conversely, increasing the solvent concentration from 0.6 to 0.7 (v v-1) increased the yield, but beyond this, lower yield was obtained. Likewise, yield increased when the extraction time was increased from 5 to 7 minutes but decreased subsequently when extraction was extended to 10 minutes. Temperature did not show significant effect on yield. Among the factors tested the solvent- to-solid ratio has the most significant effect on yield, followed by solvent concentration and extraction time while temperature had no significant effect. In the Taguchi design the highest yield of 304.90±0.58 mg GAE L-1 was obtained at 90°C, extraction time of 7 minutes, solvent-to-solid ratio of 2.5 mL g-1 and solvent concentration of 0.8 (v v-1). Using the same extraction temperature and time and solvent-to-solid ratio but lower solvent concentration, the confirmatory run resulted is significantly higher yield of 854.35±3.35 mg GAE L-1. Chlorogenic acid was identified in the extract at a concentration of 3152 mg L-1. By applying Soxhlet extraction using the same solvent concentration and solvent-to-solid ratio at the same temperature as that of the confirmatory run the yield was significantly lower at 570.42±5.3 mg GAE L-1.